The Mechanism of Arsenic Release in Contaminated Paddy Soil with Added Biochar: The Role of Dissolved Organic Matter, Fe, and Bacteria - Jianxin Fan; Maoyu Liao; Ting Duan; Ying Hu; Jiaoxia Sun (Toxics)
The addition of biochar inevitably modifies the acidity (pH), redox potential (Eh), and dissolved organic matter (DOM) level in the soil. These alterations also have coupled effects on the cycling of iron (Fe) and the composition of bacterial communities, thereby impacting the speciation and availability of arsenic (As) in the soil. This study explored the potential mechanisms through which biochar affects As in paddy soil during flooded cultivation with different pyrolysis temperature biochars (300 °C, 400 °C, and 500 °C) added. The results revealed that the TAs concentration increased in the initial 15 days of soil cultivation with SBC300 or SBC400 addition because increasing the concentration of DOM induced the mobility of As though the formation of As-DOM complexes. Meanwhile, biochar addition elevated the pH, decreased the Eh, and promoted the transformation of specific adsorbed As (A-As) and amorphous iron oxide-bound As (Amo-Fe-As) to supernatant As through enhancing the reductive dissolution of Fe(oxy)(hydr)oxides. Moreover, the biochar altered the relative abundance of As (V)-reducing bacteria (such as Firmicutes) and As (III)-oxidizing bacteria (such as Chloroflex), thereby affecting As speciation. However, these mechanistic effects varied depending on the pyrolysis temperature of the biochar. The microbial composition of SBC300 and SBC400 were similar, with both containing larger populations of Enterobacteriaceae (AsRB) and pseudomonas (FeRB) compared to CK and SBC500. It was proposed that lower pyrolysis temperatures (300 °C and 400 °C) are more favorable for the dissolution of Fe(oxy)(hydr)oxides and the reduction of As (V). However, the biochar from the higher pyrolysis temperature (500 °C) showed environmental impacts akin to the control group (CK). This study demonstrated potential mechanisms of biochar’s effect on As and the role of pyrolysis temperature.